2000
DOI: 10.1016/s0304-3959(99)00275-4
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality as an adjunctive pain control during burn wound care in adolescent patients

Abstract: For daily burn wound care procedures, opioid analgesics alone are often inadequate. Since most burn patients experience severe to excruciating pain during wound care, analgesics that can be used in addition to opioids are needed. This case report provides the first evidence that entering an immersive virtual environment can serve as a powerful adjunctive, nonpharmacologic analgesic. Two patients received virtual reality (VR) to distract them from high levels of pain during wound care. The first was a 16-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
341
2
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 519 publications
(358 citation statements)
references
References 21 publications
12
341
2
3
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] It appears that VR may change how the brain physically registers pain, not just the perception of pain stimuli. 2 An interesting study showed that 86% of patients undergoing wound care from a burn injury reported severe to excruciating pain even with therapeutic levels of opioids.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] It appears that VR may change how the brain physically registers pain, not just the perception of pain stimuli. 2 An interesting study showed that 86% of patients undergoing wound care from a burn injury reported severe to excruciating pain even with therapeutic levels of opioids.…”
mentioning
confidence: 99%
“…Hoffman et al first reported that VR could alleviate pain perception during painful burn care in adolescent patients [6]. The application of VR for pain control during burn care has been the most intensively studied application [7][8].…”
Section: Virtual Reality and Pain Managementmentioning
confidence: 99%
“…However, it is well-known that distraction-for example, having the patient listen to music-can help to reduce pain for some people. Hoffman, Doctor, Patterson, Carrougher, and Furness (2000) conducted a controlled study of the efficacy of VR as an advanced distraction by comparing it with the efficacy of a popular Nintendo video game. The results showed dramatic reductions in pain ratings during VR in comparison with those during the video game.…”
Section: Technology Presence and Flowmentioning
confidence: 99%
“…In particular, they found direct modulation of pain responses within the brain during VR distraction. The degree of reduction in pain-related brain activity ranged from 50% to 97% (Hoffman, Doctor, et al, 2000).…”
Section: Technology Presence and Flowmentioning
confidence: 99%